TEXT AS THE MAIN FORM OF KNOWLEDGE CONTROL STUDENTS WITHIN THE CREDIT-MODULAR LEARNING SYSTEMS - Smolova, S.O. (Pedagogy of Higher and Secondary Education, 2022)
The article deals with some peculiarities in using testcontrol as the means o f mostly objective grading o f students’ knowledge.